Reviewing for Interdisciplinary and Broad-Scope Journals: An Editor's Perspective. Issue 2 (1st December 2019) - Abrams, Benjamin
Abstract : If there is a single academic craft that is most sorely neglected in doctoral programs, most infrequently honed over the course of one's career, and most inconsistently exhibited at the top ranks of the academy, it is the practice of reviewing an article. Reflecting on conversations with editorial colleagues at Contention and other broad-scope journals, this essay draws together some brief guidelines on how best to compose the three most basic components of any academic review: criticism, praise, and recommendations to the editor.